Staff management and information work (Anmol Pubications, 2001)
Contents of material: 1/ Introduction. 2/ Workforce planning. 3/ Job analysis. 4/ Staff recruitment. 5/ Staff appraisal. 6/ Staff training. 7/ Staff supervission